Effect of Salt Concentration and Extremely Halophilic Archaea on the Safety and Quality Characteristics of Traditional Salted Anchovies. Issue 5 (28th May 2017) - Alfonzo, Antonio; Randazzo, Walter; Barbera, Marcella; Sannino, Ciro; Corona, Onofrio; Settanni, Luca; Moschetti, Giancarlo; Santulli, Andrea; Francesca, Nicola
ABSTRACT: Extremely halophilic archaea (EHA) might play an important role in salted fish production. So far, limited information has been available on the effect of EHA and salt concentration on the safety and quality characteristics of salted anchovies. Eight Halobacterium salinarum strains were isolated from different sea salt samples and subjected to phenotypic and genotypic characterization. The strains were then inoculated into fresh salt before addition to anchovies. A total of 18 experimental productions were performed. The inoculated trials showed the lowest counts of undesired microorganisms. In particular, salted anchovies produced with Hbt. salinarum H11 showed the lowest histamine concentration as well as the highest sensory scores. Differences in terms of volatile organic compounds (VOCs) were estimated among trials. Furthermore, multivariate analysis showed that experimental production performed with a reduced amount of salt (175 g of sea salt per kg of anchovies) did not affect the final quality of salted anchovies. The strain Hbt. salinarum H11 produced salted anchovies with well-appreciated organoleptic features. Thus, the addition of EHA and the use of a lower amount of sea salt might represent a valuable alternative to the traditional method for production of salted anchovies.